A biostatistical support system in health sciences is this sustainable in a resourcerestricted environment - Libhaber, Elena; Chirwa, Tobias; Kramer, Beverley (My University, 2023)
Background: Training in biostatistics is important for strengthening capacity in health research. This is particularly true for Africa, where research output in the health sciences has been low. Training initiatives for the continent are therefore essential. The aim of the present study was to analyse the quality and financial sustainability of the expanded biostatistical support system at a South African health sciences institution between 2013 and 2017. Methods: A cross-sectional investigation of the initiatives created between the years 2013 and 2017 in the University of the Witwatersrand, Faculty of Health Sciences Research Office was undertaken. An assessment of the one-on-one consultations carried out by postgraduate students and staff, financial costs of the support system and the number of postgraduate student graduations were analysed. Results: The number of statistical consultations increased over the period examined. The consultations were highly recommended by the postgraduate students and staff (consulters). A clear rise in the number of Masters and PhD student graduates and an increase in research units were observed from 2013 to 2017, although these cannot be solely associated with the biostatistical support system. The finances for maintaining the support system are cost effective as the number of graduates increases. The total cost to the Research Office is US$ 225 per graduate per annum. Conclusions: The expansion of the biostatistical support system has indirectly contributed to an increased number of graduates and research publication units in the institution. While the current finances support the system, any increases in enrolments or growth in diversification of biostatistical requirements may place a strain on the financial sustainability. This service is of value to developed and developing countries.
Keywords: Biostatistics; Biostatistical support system; Research training; Financial sustainability; SDG-4: Quality education